Pengaruh Variasi Konsentrasi Asam Sulfat pada Proses Hidroksilasi Minyak Jarak (Castor Oil) - Marlina Marlina; N. M. Surdia; Cythia Linaya Radiman; S. Achmad (Institut Teknologi Bandung, 2004)
Castor oil is derived from the bean of castor plant Ricinus communis L., belonging to Euphorbiaceae family from Nangroe Aceh Darussalam. Oil rendement per gram of castor bean is 45 â 52% with high purity and better than the standard oil given by AOAC. Acetylation and methylation protective process occurs on hydroxyl group of castor oil, indicated by decreasing of hydroxyl number, and also changing the structure of oil. Hydration process is more efective on acetylation-protective oil than that on non-protective and methylation-protective oil. Optimum condition reached when acid (H2SO4) concentration was 5% for non protective, 20% for acetylation protective and 15% for methylation protective oil. At those conditions, iodine and hidroxy values for non-protective, acetylation-protective, and methylation protective oil were 56.0 and 730.3; 23.3 and 664.5; and 38.5 and 649.8 mg/g, respectively.